2021
DOI: 10.1016/j.isci.2021.102906
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption ionization mass spectrometry profiling of plasma exosomes evaluates osteosarcoma metastasis

Abstract: Summary Osteosarcoma is the most common primary sarcoma of bone among adolescents, often characterized by early lung metastasis resulting in high mortality. Recently, exosomes have been used in liquid biopsy to monitor tumors. Herein, we used matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) to profile human plasma exosomes for the evaluation of osteosarcoma lung metastasis. Forty patients with osteosarcoma with (n = 20) or without (n = 20) lung metastasis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 86 publications
(92 reference statements)
0
24
0
Order By: Relevance
“…However, it puts forward high demands on exosome sample pretreatment and faces a great challenge when encountering the clinical disease metabolomics toward precision medicine, which requires rapid and high-throughput detection of thousands of biological samples. Owing to the convenient sample preparation, trace sample consumption, short analysis time, high throughput, and accuracy, laser desorption/ionization mass spectrometry (LDI-MS) is attracting increasing interest in large-scale clinical applications. LDI-MS is primitively designed for analyzing biological macromolecules with the assistance of traditional organic matrices such as 2,5-dihydroxybenzoic acid (DHB) and α-cyano-4-hydroxycinnamic acid (CHCA). Recently, researchers attempted to separate exosomes beforehand by ultracentrifugation or co-precipitation and then employ traditional organic matrices assisted LDI-MS to profile exosome proteinic patterns, , manifesting the combination potential of LDI-MS and exosomes in diagnostics. However, ultracentrifugation or co-precipitation separation are high-cost and time-consuming .…”
Section: Introductionmentioning
confidence: 99%
“…However, it puts forward high demands on exosome sample pretreatment and faces a great challenge when encountering the clinical disease metabolomics toward precision medicine, which requires rapid and high-throughput detection of thousands of biological samples. Owing to the convenient sample preparation, trace sample consumption, short analysis time, high throughput, and accuracy, laser desorption/ionization mass spectrometry (LDI-MS) is attracting increasing interest in large-scale clinical applications. LDI-MS is primitively designed for analyzing biological macromolecules with the assistance of traditional organic matrices such as 2,5-dihydroxybenzoic acid (DHB) and α-cyano-4-hydroxycinnamic acid (CHCA). Recently, researchers attempted to separate exosomes beforehand by ultracentrifugation or co-precipitation and then employ traditional organic matrices assisted LDI-MS to profile exosome proteinic patterns, , manifesting the combination potential of LDI-MS and exosomes in diagnostics. However, ultracentrifugation or co-precipitation separation are high-cost and time-consuming .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, proteomic profiling of EVs utilizing the technique used in the current investigation (i.e., MALDI-TOF MS) can be sensitive. A study by Han and colleagues demonstrates the utility of this methodology by using the MALDI-TOF mass spectra of plasma-derived EVs to identify those patients with or without osteosarcoma lung metastasis [26]. While we reveal possible slight differences in the protein make-up ( Figure 6D ), we only investigated the surface proteins of undigested EV samples and thus further proteomic analyses (i.e., LC-MS) may reveal more significant differences.…”
Section: Discussionmentioning
confidence: 90%
“…Each EV sample was mixed 1: 1 with sinapic acid matrix (Millipore Sigma, 85429; 20 mg/mL in 50% acetonitrile, 50% water, 0.1% trifluoracetic acid v/v/v) and 1 μl of the sample/matrix solution was deposited on a MicroFlex AnchorChip plate (Bruker, Bremen, Germany) in triplicate and dried in a vacuum. The analysis was performed under linear positive mode using the following parameters as previously described [26]: 70% laser intensity, laser attenuator with 35% offset and 40% range, accumulation of 500 laser shots, and 10.3 detector gain. Mass calibration was completed using cytochrome c (2 mg/mL; Sigma Aldrich, C8857) and myoglobin (2 mg/mL; Sigma Aldrich, M0630).…”
Section: Methodsmentioning
confidence: 99%
“…On the mature foundation of MALDI-TOF MS fingerprinting technology, many other samples have been used for biomarker discovery and cancer diagnosis, especially exosomes isolated from body fluids. , In 2019, Zhu et al used MALDI-TOF MS to analyze exosomes extracted from serum of melanoma patients and healthy donors and demonstrated that the mass fingerprinting of bloodstream-circulating exosomes can be used for cancer diagnosis and monitoring . In 2021, Han et al used MALDI-TOF MS to analyze serum exosomes from 12 healthy donors, 20 osteosarcoma patients without lung metastasis, and 20 osteosarcoma patients with lung metastasis.…”
Section: Clinical Application and Potential Of Maldi-tof Msmentioning
confidence: 99%